2004
DOI: 10.2308/jmar.2004.16.1.183
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Customer Loyalty and Financial Performance

Abstract: Recent research in accounting advocates nonfinancial measures of company performance, such as customer satisfaction and loyalty, as useful indicators of aspects of firm performance. But what are the drivers of customer satisfaction and loyalty? We provide an integrated causal model of company performance in the personal computer (PC) industry that simultaneously tests links between product value attributes resulting from business process performance, customer loyalty, and financial outcomes. Our results extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
2
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(131 citation statements)
references
References 20 publications
3
114
2
12
Order By: Relevance
“…A number of previous studies have found mixed results in regard to a relationship between performance and customer retention, customer satisfaction, customer loyalty and sophisticated management accounting practices (Agbejule, 2005;Banker et al, 2000, Ittner andLarcker, 1998;Smith and Wright, 2004;and Qianpin, 2010). Even so, it was found in this study that large hotels, with decentralised structures, highly market orientated together with undertaking a prospector strategy, will use customer satisfaction analysis, and together there will be a positive impact on the hotels' non-financial performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of previous studies have found mixed results in regard to a relationship between performance and customer retention, customer satisfaction, customer loyalty and sophisticated management accounting practices (Agbejule, 2005;Banker et al, 2000, Ittner andLarcker, 1998;Smith and Wright, 2004;and Qianpin, 2010). Even so, it was found in this study that large hotels, with decentralised structures, highly market orientated together with undertaking a prospector strategy, will use customer satisfaction analysis, and together there will be a positive impact on the hotels' non-financial performance.…”
Section: Resultsmentioning
confidence: 99%
“…Ittner and Larcker (1998) found significant relationships between customer satisfaction and customer retention, revenues and revenue changes within one large telecommunications firm, yet only a significant relationship between customer satisfaction and revenue for a financial services firm. Similarly, Banker, Potter and Srinivasan (2000) reported mixed results for the association between customer satisfaction and financial performance in a single hotel firm, and Smith and Wright (2004) found that in the personal computer industry, higher customer loyalty (seen as a proxy for customer satisfaction) is related to higher average product price, sales growth and return on assets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…al., 2002). Smith and Wright (2004) used product quality, service quality, and firm viability in their structural equation model as direct determinants of customer loyalty in the personal computer industry, found service quality and firm viability to be statistically significant and product quality was negatively associated with customer loyalty. Hee-Su and Yoon (2004) in a research in the mobile industry researched if a mobile telephone subscriber would refer the carrier to others found that; call quality (service quality), customer mobile equipment type (product quality and features), and brand image were variables that had significant (positive) effect on customer loyalty.…”
Section: Customer Loyaltymentioning
confidence: 99%
“…Customers have more customized expectations and want to be reached as individuals (Raymond & Tanner, 1994). In addition, an exorbitant search for new business is costly (Carter, 2010).…”
Section: Customer Retention Strategiesmentioning
confidence: 99%